Audit as a Catalyst: Enhancing the Impact of Sustainable Management Accounting on Islamic Bank Performance - Ompusunggu, Hermaya; Mustika, Ita; Richmayati, Maya; Khadijah, Khadijah; Yuniati, Sasmita (AKTSAR: Jurnal Akuntansi Syariah, 2025)
This study examines the effect of Sustainable Management Accounting (SMA) on the performance of Islamic banks, with the audit function as a moderator. Based on Legitimacy Theory, this study explains how SMA practices—which integrate environmental, social, and ethical aspects into budgeting, cost control, and performance measurement—improve financial and non-financial performance. This study employs a quantitative approach, utilising primary data. The population in this study consists of managers, internal auditors, and members of the Sharia Supervisory Board of Islamic banks in the Riau Islands Province, totalling 102 respondents. The data analysis used is SEM-PLS. The results show that SMA has a significant positive effect on performance, and the audit function strengthens this relationship. The findings confirm that high audit quality enhances the effectiveness of SMA, transparency, and stakeholder trust. This study expands the Legitimacy Theory and recommends integrating SMA with strong audit oversight to enhance governance and long-term value.